2020
DOI: 10.2105/ajph.2019.305441
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Needs for Advancing the Profession and Workforce in Environmental Health

Abstract: An ever-changing landscape for environmental health (EH) requires in-depth assessment and analysis of the current challenges and emerging issues faced by EH professionals. The Understanding the Needs, Challenges, Opportunities, Vision, and Emerging Roles in Environmental Health initiative addressed this need. After receiving responses from more than 1700 practitioners, during an in-person workshop, focus groups identified and described priority problems and supplied context on addressing the significant chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…While EHOs have been prioritising the implementation, education and regulation of social distancing measures, it is essential that exacerbated and emerging threats such as methamphetamine contamination of properties are not overlooked. Sufficient resources, support and recognition of the EHO workforce will enable them to identify and mitigate risks early to minimise long‐term public health consequences 14,60,61 …”
Section: Resultsmentioning
confidence: 99%
“…While EHOs have been prioritising the implementation, education and regulation of social distancing measures, it is essential that exacerbated and emerging threats such as methamphetamine contamination of properties are not overlooked. Sufficient resources, support and recognition of the EHO workforce will enable them to identify and mitigate risks early to minimise long‐term public health consequences 14,60,61 …”
Section: Resultsmentioning
confidence: 99%
“…41 In addition, addressing the rapidly emerging EH problems require updated knowledge and skills of professionals. 11 Remarks related to the need for increased professional development and training was made. The finding of this study revealed that professionals with Master's degree were 13.4 times more likely to identify environmental problems compared to their counter parts (AOR = 13.4 with 95% CI: 0.9-5.9).…”
Section: Environmental Health Insightsmentioning
confidence: 99%
“…22 The role of this profession has rapidly evolved over recent years to include emergencies to protect the public from exposures to environmental hazards, disasters, and disease outbreaks. 23 In recognition, the profession has been formally recognized in the Pandemic and All-Hazards Preparedness and Advancing Innovation Act of 2019. In this situation, the activities would build on existing skills and tasks.…”
Section: Mass Gathering Reopening Considerationsmentioning
confidence: 99%